1999
DOI: 10.1093/humrep/14.8.1962
|View full text |Cite
|
Sign up to set email alerts
|

Blind hemivagina: long-term follow-up and reproductive performance in 42 cases

Abstract: Our purpose was to analyse the reproductive performance of women with obstructed hemivagina after surgical treatment. After laparoscopic exploration of 42 cases (mean age: 18 years), didelphic and complete septate uterus were found in 78 and 22% of cases respectively. Resection of vaginal septum and hemihysterectomy with ipsilateral hemicolpectomy were performed in 88% and 12% of the cases, respectively, between 1970 and 1997. Long-term results were assessed by a questionnaire and obtained for 38 patients (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 18 publications
1
79
3
5
Order By: Relevance
“…5 As it includes only two of the three components of the triad, it enables the inclusion of uterine anomalies, other than the more common uterus didelphys, such as a completely septated uterus (in up to 22% of cases, in some series). 10 Given the lack of uniformity in the denomination of the syndrome, review of the literature is also difficult. For example, although the word ''septum'' usually describes the midline longitudinal and nonobstructive septum of the isolated uterus didelphys, in the context of the abovementioned triad it has been used to describe the medial wall of the upper unilateral hematocolpos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 As it includes only two of the three components of the triad, it enables the inclusion of uterine anomalies, other than the more common uterus didelphys, such as a completely septated uterus (in up to 22% of cases, in some series). 10 Given the lack of uniformity in the denomination of the syndrome, review of the literature is also difficult. For example, although the word ''septum'' usually describes the midline longitudinal and nonobstructive septum of the isolated uterus didelphys, in the context of the abovementioned triad it has been used to describe the medial wall of the upper unilateral hematocolpos.…”
Section: Discussionmentioning
confidence: 99%
“…Several series reported other anomalies or even patients with two normal kidneys. 5,7,8,10 Smith and Laufer, in the largest series limited to modern management described to date, including 27 cases of obstructed hemivagina and ipsilateral renal anomaly, reported: 20 cases of ipsilateral renal agenesis (74%), 1 case of dysplastic and 1 case of polycystic kidney, 3 cases of bilateral normal kidneys, 1 contralateral duplex collecting system, 1 urethral diverticulum, and 1 rectovesical band. 5 Other anomalies, such as an ectopic ureter, have also been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this septum is obstructive on one side, this is almost invariably associated with ipsilateral renal or ureteric anomalies. To the best of our knowledge, only three cases of didelphic uterus and obstructed hemivagina with normal urinary tracts have been reported in the literature [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that endometriosis occurs more frequently in patients with didelphic uterus, probably due to retrograde menstruation [14]. A retrospective study of 41 cases of obstructed hemivagina found associated complications including hematosalpinx, pyosalpinx, pelvic adhesions, and endometriosis in 39% of cases [5].…”
Section: Discussionmentioning
confidence: 99%